Features of cerebral hemodynamics and vascular autoregulation in chronic cerebral ischemia - O.A. Kozyolkin; S.V. Yarkova (Zaporozhye State Medical University, 2013)
Introduction. The problem of cerebrovascular diseases in Ukraine and the world is one of the urgent problems of modern clinical medicine. The most wide-spread such a disease is chronic ischemic attack. These aspects determine the relevance of studying the problem of vascular diseases of the brain. The role of disturbances of cerebral hemodynamics is important in the formation of chronic cerebral ischemia. Recent years, the importance of the development of vascular disease is provided by endothelial dysfunction. The endothelium synthesizes active substances. The most significant of these ones is nitric oxide. Substrate for the synthesis of nitric oxide is L-arginine. High level of L-arginine in plasma leads to nonspecific vasodilatation. Thus, the use of L-arginine is promising in the treatment of patients with chronic cerebral ischemia. The purpose of the study. Improvement of diagnostic and therapeutic interventions for patients with DE II by examining the clinical, hemodynamic features and application of L-arginine in the treatment . Materials and methods. The study involved 84 patients. 62 of these patients are sick with dyscirculatory encephalopathy II stage (DE) against the background of cerebral arteriosclerosis, hypertension . The groups of patients who were treated with L-arginine (20 patients) and control group (18 patients) were formed. The following studies were performed for the patients: clinical and neuropsychological examination and duplex scanning of brachiocephalic, transcranial vessels by duplex-triplex scanner LOGIQ C- 5 Premium. Results. The clinical situation of the main group and the control group treatment represents such syndromes: syndrome of headache (88.71 %), vestibular ( 74.19 %) , asthenia ( 58.06 %), mild ( 30.65 %) and moderate (69, 35%) cognitive impairment. While analyzing the hemodynamic performance of the study group a statistically significant increasing of linear flow velocity (LFV) in all basins, cerebrovascular reserve extension were observed after treatment. It should be noted that after treatment a significant increase of LFV in the study group was recorded compared with those before treatment and compared with the control group. In the control group improved speed performance is also noted, but it is not credible. In the patients of main group subjective and objective improvement in reducing complaints of headache, dizziness, fatigue was noted. Conclusions. The studies demonstrate the effectiveness of L-arginine in treatment of chronic cerebrovascular disease. In patients who received L-arginine improvement in general health, reducing symptoms of headache, dizziness were recorded. Improvement of hemodynamics was noticed, due to its influence on the synthesis of endothelium-relaxing factor. Given the multifaceted therapeutic effect of L-arginine, the medicine should be recommended for using in the treatment of patients with stage II DE .